Laparoscopic near-infrared fluorescent imaging as an alternative option for sentinel lymph node mapping in endometrial cancer: A prospective study - Taskin, Salih; Sukur, Yavuz Emre; Altin, Duygu; Ersoz, Cevriye Cansiz; Turgay, Batuhan; Kankaya, Duygu; Gungor, Mete; Ortac, Firat (ELSEVIER SCIENCE BV, 2017)
Background: To evaluate feasibility of sentinel lymph node (SLN) mapping by using near-infrared fluorescent imaging and indocyanine green (NIR/ICG) integrated laparoscopic system in clinically uterine-confined endometrial cancer. Materials and methods: Patients with clinically early-stage endometrial cancer were included in this prospective study. ICG was injected to the uterine cervix and NIR/ICG integrated laparoscopic system (Spies Full HD D-Light P ICG technology, Karl Storz, Tuttlingen, Germany) was used during the operations. SLN and/or suspicious lymph nodes were resected. Side specific lymphadenectomy was performed when mapping was unsuccessful. Systematic lymphadenectomy was completed following SLN algorithm steps. Results: Seventy-one eligible patients were analyzed. The overall, unilateral and bilateral SLN detection rates were 95.7\%, 18.3\%, 77.4\%, respectively. There were 8 (11.2\%) patients with lymph node metastasis. One of them was isolated para-aortic node metastasis. Negative predictive value, sensitivity and false negative rate for detecting lymphatic spread were 98.4\%, 87.5\% and 1.5\%, respectively. Conclusion: Sentinel lymph node mapping can easily be performed with high accuracy by using NIR/ICG integrated conventional laparoscopic system in endometrial cancer and almost all lymphatic spread can be detected. (C) 2017 IJS Publishing Group Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: Endometrial cancer; Indocyanine green; Laparoscopy; Sentinel lymph node